UM ESTUDO SOBRE A INTERDISCIPLINARIDADE COM PRÁTICAS COM MODELAGEM MATEMÁTICA NA EDUCAÇÃO BÁSICA - Forteski, Daiane (2019)
With this study we seek to investigate the interdisciplinary potential of mathematical modeling practices in the classroom. The research was developed in a rural school with third year high school students, having as object of study the work in the classroom from the perspective of Burak (1992). For this study, we formulated the following research question: What is shown about Interdisciplinarity from practices with Mathematical Modeling? The study was a case study, tried in a third year high school class in a school in Campo. Data processing followed the steps of content analysis described by Bardin (2009). We elect as general objective to point out the interdisciplinary correlations that occur during a practice with Modeling. In this way we analyze the characteristic elements of interdisciplinarity described by Pombo (2008) and Fazenda (1994), in the development of the actions lived by three groups of students on the themes: Technology, Measurements of the Human Cup and Cells. The results show that teaching through Mathematical Modeling is able to establish meaningful interlocutions between the areas of knowledge, thus leading to an interdisciplinary approach. The steps described for this methodology were presented as means to enhance a broader and global view of knowledge.